Experimental investigation of swirl number influence on spiral vortex structure dynamics. Issue 1 (June 2021) - Štefan, D; Hudec, M; Uruba, V; Procházka, P; Urban, O; Rudolf, P
Abstract: The hydraulic turbines are recently forced to operate far away from the optimal conditions in order to balance fluctuations in electricity generation. In case of Francis, pump and propeller turbines, using only single control component of guide vanes, it means that in regions where the high residual swirl enters the draft tube, the flow is decelerated and convenient conditions for the vortex rope development are created. Such flow conditions are considered to be the triggering mechanism for occurrence of different forms of vortex structures in the Francis turbine draft tube, e.g. spiral or straight vortex rope at part load or full load respectively. Independently on the vortex rope shape the unsteady pressure fields develop producing periodic stress on turbine components and possibly resulting in noise, blade cracks, runner lift, power swing, etc. To study and mimic such flow conditions, a simplified device of vortex generator apparatus is employed. Thanks to its design, the vortex generator enables to change the ratio between fluxes of axial momentum and tangential moment of momentum of generated swirl. Then, the behavior of vortex structure changes in a similar way as the flow rate variation in the draft tube of Francis turbine. For above mentioned reasons the unsteady cavitating spiral vortex is experimentally studied using both high speed video record and particle image velocimetry (PIV). The main focus is on change of vortex dynamics regarding to the swirl number variation. The proper orthogonal decomposition (POD) together with the classical fast Fourier transformation (FFT) are employed to extract dominant modes and frequencies from experimental data.